First, remove all of the terms from parenthesis on both sides of the equation. Be careful to handle the signs of each individual term correctly:
#3 - 2 + x = 6 - 2x - 1#
Next, group and combine like terms on each side of the equation:
#(3 - 2) + x = 6 - 1 - 2x#
#(3 - 2) + x = (6 - 1) - 2x#
#1 + x = 5 - 2x#
Then, subtract #color(red)(1)# and add #color(blue)(2x)# to each side of the equation to isolate the #x# term while keeping the equation balanced:
#-color(red)(1) + 1 + x + color(blue)(2x) = -color(red)(1) + 5 - 2x + color(blue)(2x)#
#0 + 1x + color(blue)(2x) = 4 - 0#
#(1 + color(blue)(2))x = 4#
#3x = 4#
Now, divide each side of the equation by #color(red)(3)# to solve for #x# while keeping the equation balanced:
#(3x)/color(red)(3) = 4/color(red)(3)#
#(color(red)(cancel(color(black)(3)))x)/cancel(color(red)(3)) = 4/3#
#x = 4/3#